2009
DOI: 10.1111/j.1365-2044.2008.05824.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the LMA Supreme in 100 non‐paralysed patients*

Abstract: SummaryWe studied the LMA Supreme TM in 100 elective, anaesthetised, healthy patients assessing: ease of use, airway quality, anatomical and functional positioning, airway leak and complications. Insertion was successful on first, second or third attempt in 90, nine and one patient respectively. Thirty manipulations were required in 22 patients to achieve a clear airway. Median [interquartile (range)] insertion time was 18 [10-25 (5-120)] s. During ventilation, an expired tidal volume of 7 ml.kgwas achieved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
76
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 29 publications
18
76
1
2
Order By: Relevance
“…We assume that relatively larger size SLMA might have been the cause of difficult insertion in those 3 cases. The range of insertion time (TOI) in our study was 11-15 seconds, which is supported by similar findings by Verghese C et al [7] , Cook TM et al [11] and Theiler LG et al [14] . We think that the intelligent design of the fixation tube (FT) along with the elliptical and anatomically shaped semi rigid airway tube of the SLMA facilitated rapid insertion.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We assume that relatively larger size SLMA might have been the cause of difficult insertion in those 3 cases. The range of insertion time (TOI) in our study was 11-15 seconds, which is supported by similar findings by Verghese C et al [7] , Cook TM et al [11] and Theiler LG et al [14] . We think that the intelligent design of the fixation tube (FT) along with the elliptical and anatomically shaped semi rigid airway tube of the SLMA facilitated rapid insertion.…”
Section: Discussionsupporting
confidence: 91%
“…Our study was designed to observe the insertion qualities, hemodynamic changes and post-insertion complications of SLMA in the pediatric population. In our study SLMA could be inserted in the first attempt in 90% of cases, which is exactly same, found by Timmermann A et al [10] and Cook TM et al [11] in their studies. The rigid anatomically shaped airway tube of the SLMA facilitates easy insertion of the device without the need for insertion of the fingers of the user into the patient's mouth.…”
Section: Discussionsupporting
confidence: 91%
“…The degree of airway obstruction (no obstruction, intermittent partial obstruction, intermittent complete obstruction or complete obstruction) [11], if encountered, and the number and type of airway manoeuvers (including jaw thrust, head/neck extension and/or device adjustments such as advancement/withdrawal of device, and alterations to cuff volume) required to maintain airway patency were also documented.…”
Section: Methodsmentioning
confidence: 99%
“…In clinical trials, the SLMA has been found comparable with the reusable LMA ProSeal TM (PLMA), 1 with the SLMA having a higher rate of success on first attempt insertion. [2][3][4][5] Previous studies have shown the use of the PLMA and SLMA in non-paralyzed patients, 6 in anesthetized patients with a simulated difficult airway, 7 and in patients undergoing laparoscopy procedures. 8,9 More recent studies and case reports have shown that it is effective in providing ventilation and oxygenation in challenging cases, such as the morbidly obese patients, 10 patients in the prone position, 11,12 and those who have suffered from multiple trauma.…”
Section: Résumémentioning
confidence: 99%